A hydroeconomic modeling framework for optimal integrated management of forest and water. Issue 10 (27th October 2016) - Garcia‐Prats, Alberto; del Campo, Antonio D.; Pulido‐Velazquez, Manuel
Abstract: Forests play a determinant role in the hydrologic cycle, with water being the most important ecosystem service they provide in semiarid regions. However, this contribution is usually neither quantified nor explicitly valued. The aim of this study is to develop a novel hydroeconomic modeling framework for assessing and designing the optimal integrated forest and water management for forested catchments. The optimization model explicitly integrates changes in water yield in the stands (increase in groundwater recharge) induced by forest management and the value of the additional water provided to the system. The model determines the optimal schedule of silvicultural interventions in the stands of the catchment in order to maximize the total net benefit in the system. Canopy cover and biomass evolution over time were simulated using growth and yield allometric equations specific for the species in Mediterranean conditions. Silvicultural operation costs according to stand density and canopy cover were modeled using local cost databases. Groundwater recharge was simulated using HYDRUS, calibrated and validated with data from the experimental plots. In order to illustrate the presented modeling framework, a case study was carried out in a planted pine forest ( Pinus halepensis Mill.) located in south‐western Valencia province (Spain). The optimized scenario increased groundwater recharge. This novel modeling framework can be used in the design of a "payment for environmental services" scheme in which water beneficiaries could contribute to fund and promote efficient forest management operations. Key Points: Hydrology‐oriented silviculture is proposed to manage semiarid forest with a specific focus on forest‐water interactions Hydroeconomic models allow to explore integrated water and forest management strategies that maximize total value of water use in the system Groundwater recharge may be controlled through forest management